Severe Acute Thrombocytopenia After Treatment with Tirofiban: A Case Series Approach - Gian-Manuel Jiménez-Rodríguez; Patricia Carmona-Levario; José-Alberto Ayón-Martínez; Aleksandra Gasecka; Luis Eduardo Juárez-Orozco; Antonio Reyes-Ortega; Patricia Espinosa-González; Gyna Alejandra Altamirano-Solorzano; Guering Eid-Lidt (Interventional Cardiology: Reviews, Research, Resources)
Glycoprotein IIb/IIIa inhibitors are an adjuvant therapy for the treatment of patients with acute coronary syndromes. The main adverse reactions are bleeding and thrombocytopenia in 1–2% of cases. A 66-year-old woman arrived at the emergency department with ST-elevation MI. The catheterisation lab was busy, so she received thrombolytic therapy. Coronary angiography revealed a 90% stenosis in the middle segment of the left anterior descending artery and Thrombolysis in MI 2 flow. Subsequent percutaneous coronary intervention showed abundant thrombus and a coronary dissection and it was necessary to insert five drug-eluting stents. Non-fractionated heparin and a tirofiban infusion were used. After the percutaneous coronary intervention, she developed severe thrombocytopenia, haematuria and gingivorrhagia, for which infusion of tirofiban was suspended. In follow-up, no major bleeding or subsequent haemorrhagic complications were identified. It is crucial to distinguish between heparin-induced thrombocytopenia and thrombocytopenia caused by other drugs. A high level of suspicion should be employed in these cases.